1968
DOI: 10.1039/j19680002428
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of vitamin B12. Part X. cis- and trans-Effects

Abstract: We have studied the effect of varying one axial ligand (X). usually an organo-ligand, on the stretching frequency of cyanide co-ordinated in the trans-position (Y) and on the spectrum of the equatorial corrin ring in these cyanocomplexes, and have measured several additional formation constants for substitution of the axial ligands. The cyanide stretching frequency is very dependent on the nature of X, falling from 21 32 cm.-l when X = benzimidazole to 2082 cm.-l when X = CH3CH2-. All the evidence relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…It is reported that band A is attributable to the C-N stretching of vitamin B 12 with respect to the trans axial ligand. 37 The results suggest that the C-N bond in the vitamin B 12 molecule was cleaved within 80 min. Band B was shifted from 1666 to 1638 cm -1 , which is a suitable marker for monitoring the reactions of the side chains of vitamin B 12 during photodegradation.…”
Section: Investigation Of Reaction Kineticsmentioning
confidence: 92%
“…It is reported that band A is attributable to the C-N stretching of vitamin B 12 with respect to the trans axial ligand. 37 The results suggest that the C-N bond in the vitamin B 12 molecule was cleaved within 80 min. Band B was shifted from 1666 to 1638 cm -1 , which is a suitable marker for monitoring the reactions of the side chains of vitamin B 12 during photodegradation.…”
Section: Investigation Of Reaction Kineticsmentioning
confidence: 92%
“…3, a six-coordinate aqua complex may also be involved in a formal sense as an intermediate in the equilibrium of DBI displacement upon acidification of cobalamins, but Firth et al reported that the proportion of a six-coordinate aqua complex in neutral aqueous solution is negligible with AdoCbl and ethylCbl (15). They demonstrated as well with organo-Cbls that a strong -donor ligand increases an equilibrium constant (K)-that is, it favors the formation of a fi vecoordinate complex (14). Therefore, the above-mentioned order of apparent pKa values of acyl-Cbls seems to be reasonable by assuming the equilibrium shown in Eq.…”
Section: Identifi Cation and Chromatographic Electrophoretic And Spmentioning
confidence: 99%
“…The net charges of alkyl-and acyl-Cbls refl ect their baseon → ← base-off equilibria (Eq. 3) at this pH, suggesting that the so-called trans-effect (14) or the -donor strength of an upper axial ligand increases in the order: formylϽacetylϽpropionyl. Although the methyl group is a stronger -donor than acyl groups, methyl-Cbl showed much smaller mobility (Table 2).…”
Section: Identifi Cation and Chromatographic Electrophoretic And Spmentioning
confidence: 99%
“…(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(4.2 x lod2) 4.5 x dm3 mol-'; i.e. logl& 2 22.7 (3)…”
unclassified